2017
DOI: 10.1007/s40520-017-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on noninvasive mechanical ventilation in elderly medical intensive care unit patients

Abstract: We identified no significant differences in NIV success when age and specific comorbidities were considered [5]. But since patient inclusion criteria of our study were not designed to investigate the answers of these questions we cannot interpret our results as these factors do not have any impact on NIV success. We can just say that both groups have similar percentages of patients with COPD and HF and there was no significant difference in their ages.On the other hand and more importantly with our results, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
1
0
2
Order By: Relevance
“…Frailty was recognized initially in the field of geriatric medicine, and it has recently been increasingly identified as an essential determinant of prognosis in patients admitted to ICU. Our results were consistent with those of a previous study which showed that frail patients were at higher risk than non-frail patients of poor outcomes in different settings ( 44 46 ). The explanation for this finding involves the changes in pathophysiology in frail patients.…”
Section: Discussionsupporting
confidence: 93%
“…Frailty was recognized initially in the field of geriatric medicine, and it has recently been increasingly identified as an essential determinant of prognosis in patients admitted to ICU. Our results were consistent with those of a previous study which showed that frail patients were at higher risk than non-frail patients of poor outcomes in different settings ( 44 46 ). The explanation for this finding involves the changes in pathophysiology in frail patients.…”
Section: Discussionsupporting
confidence: 93%
“…Dies sind im Wesentlichen dieselben Prädiktoren, die auch für den Therapieerfolg herangezogen werden. So erwiesen sich in den jeweiligen Studien ein niedriger pH-und hoher pCO 2 -Wert, eine hohe Herzfrequenz ein, erhöhter APACHE-II-Score (> 29), ein erhöhtes BNP, ein niedriger Glasgow-Coma-Scale, ein unter NIV niedriger pO 2 , begleitende Komorbiditäten, wie u. a. eine Tumorerkrankung, höheres Lebensalter mit Gebrechtlichkeit sowie vorausgegangene NIV-pflichtige Exazerbationen [29,34,44,[46][47][48][49][50][51][52][53][54] als Prädiktoren für ein NIV-Versagen. Zusätzlich konnte eine pneumonische Ursache des hyperkapnischen Atemversagens [40,55,56] als Risikofaktoren für einen ungünstigen Verlauf mit Intubation, längerem Krankhausaufenthalt und erhöhter Mortalität gefunden werden.…”
Section: Prädiktoren Des Niv-versagensunclassified
“…We report that worsening cardiac disease, in the form of cardiogenic shock and cardiac arrest, are associated with NIV failure. Shock, 29 more severe heart failure, 7,9 multisystem organ failure defined by Sequential Organ Failure Assessment (SOFA) score, 22 frailty, 30 poor mental status, 8 weak cough, 31 and higher tidal volume on NIV 29 are factors that have been reported in the literature to be associated with NIV failure. Similar to our findings, Liu and colleagues 18 also reported that older age was associated with lower risk of NIV intolerance.…”
Section: Factors Associated With Niv Failure In Ahfmentioning
confidence: 99%